Managing vulnerabilities and coping mechanisms the case of the Farmer-Scientists Training Program (FSTP) in Cebu - Seminiano, Simeona C. (UP Los Baños Journal, 2011)
The Farmer-Scientists Training Program (FSTP) is an extension program of the College of Agriculture, University of the Philippines Los Baños conducted in Cebu since 1994. It aims to give farmers direct contact with agricultural scientists to develop their technical and scientific capabilities to grow corn and other crops utilizing improved technologies. The study identified basic sources of vulnerabilities that greatly influenced the productivity of Cebu corn farmers. The socio-economic factors included lack of positive values towards modernization, services and facilities. The farmers were also vulnerable to existing marginal soil, climate and weather. The manner in how they cope with these vulnerabilities was also discussed. Through the FSTP program the farmers developed technical adeptness and business acumen. They learned how to manage their resources through partnership and to form values toward modernization. As a consequence, the technical capability acquired improved their production, income, personality and behavior resulting to a much better quality of life.